Suitability zoning of buried pipe ground source heat pump and shallow geothermal resource evaluation of Linqu County, Shandong Province, China. (October 2022) - Hu, Ziyuan; Gao, Zongjun; Xu, Xiqiang; Fang, Shaoyan; Zhou, Liangyu; Ji, Deshuai; Li, Fuquan; Feng, Jianguo; Wang, Min
Abstract: In response to the environmental call for energy conservation and emission reduction, the development and utilization of shallow geothermal energy (SGE) buried pipe ground source heat pumps (GSHP) in the urban area of Linqu County has been studied. Based on geological data and water quality analysis data, ground temperature monitoring test and field thermal response test research results, using the analytic hierarchy process, the suitability of buried GSHP in the study area is computed by division, heat capacity calculation and resource potential evaluation. The results show that the development and utilization of GSHP in the study area are mainly in the moderately suitable area. The heat capacity within 120 m depth is 3.52 × 10 13 kJ/°C, and the heat capacity of 200 m shallow geothermal energy is 5.84 × 10 13 kJ/°C. Considering the land use coefficient, the total available heat transfer power of the buried pipe ground source heat pump is 2.56 × 10 6 kW. The heat transfer power in summer is greater than the heat transfer power in winter. The resource potential of buried pipe ground source heat pump is mainly in the medium potential area, and the development potential is finer in winter than in summer. Generally, the development and utilization of shallow geothermal energy in the urban area of Linqu County have broad pros.